Orbital migration of schistosome eggs: a case report - Guirou, Nouhoum (BMC Ophthalmol, 2021)
BACKGROUND: Ocular damage, including damage to the conjunctiva, lacrimal gland, eyelids, and orbit, caused by Schistosoma haematobium is sporadic. We report a clinical case of orbital migration of schistosome eggs. CASE PRESENTATION: A 14-year-old boy of Malian nationality presented with a painless swelling of the upper right eyelid, which had been gradually increasing for approximately 3 months. Visual acuity was logMAR 0.10 and 0.00 in the right and left eye, respectively. External examination revealed a right palpebral mass, pushing the globe slightly downward and inward. Computed tomography revealed a mass of the right lacrimal gland. Total excision of the mass was performed by transpalpebral orbitotomy. Pathological examination revealed an inflammatory granulomatous infiltrate of the lacrimal gland consisting of lymphocytes, eosinophils, giant cells, epithelioid cell, histiocytes and calcified Schistosoma eggs with terminal spine. Urine examination revealed eggs of S. haematobium. Praziquantel 40 mg/kg was administered to the patient. The hematuria stopped after 1 week. After 3 years of follow-up, no recurrence was noted. CONCLUSIONS: The bilharzian granuloma of the lacrimal gland is an ectopic site of the parasite. In this case, the granuloma was cured by surgical excision followed by a course of Praziquantel.